Parents' Decision-making Experience in Choosing the MMR Vaccine in Banten, Indonesia - Nugraha Kusuma, Andiko; Nasiatin, Titin; Sansuwito, Tukimin (KnE Social Sciences, 2023)
Research has extensively studied parental vaccination decision-making drivers and barriers. The most powerful predictors of vaccination actions include the understanding of the risks posed by the disease; and the side effects of vaccination; vaccine beliefs and attitudes; and their effectiveness and safety concerns. Thus, this study aimed to explore the parents decision-making experience in choosing MMR vaccine in Banten, Indonesia. In qualitative study, a purposeful sampling process was used to identify parents with a variety of expected MMR decisions: (1) accept MMR on time, (2) accept MMR late, (3) receive one or more individuals, (4) obtain no MMR or individuals. A qualitative quality analysis was used to interpret the transcribed text. A total of 25 participants from 5 different FGDs were included in this study. This qualitative interview resulted in 4 themes, namely: healthy life, own health perceptions, disease history, perceived severity, and susceptibility of vaccine-preventable illnesses. Research on the MMR vaccination should move a step forward and include studies looking at similarities and differences in the factors predicting parents’ intention to follow MMR vaccination recommendations by comparing parents of very young children, being the primary target group of MMR vaccination campaigns and interventions, with parents of adolescent children. Keywords: decision process, MMR vaccine, qualitative study